2011
DOI: 10.1016/j.cropro.2011.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of the field-susceptibility of Sesamia nonagrioides to the Cry1Ab toxin in areas with different adoption rates of Bt maize and in Bt-free areas

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Actually, the lethal concentrations of the population from Ebro (Spain) was in the lower range of the values obtained, though Bt maize in this area represented Ϸ70% of the transgenic maize cultivated in Spain in 2004 Ð2005. This Þnding is consistent with the lack of resistant development to Cry1Ab in Spanish populations (Farinó s et al 2004(Farinó s et al , 2011. Moreover, binding site analysis performed with S. nonagrioides larvae revealed that Cry1F and Cry1Ab proteins have different high-afÞnity binding sites (González-Cabrera et al 2006), making the development of cross-resistance unlikely.…”
Section: Discussionsupporting
confidence: 80%
“…Actually, the lethal concentrations of the population from Ebro (Spain) was in the lower range of the values obtained, though Bt maize in this area represented Ϸ70% of the transgenic maize cultivated in Spain in 2004 Ð2005. This Þnding is consistent with the lack of resistant development to Cry1Ab in Spanish populations (Farinó s et al 2004(Farinó s et al , 2011. Moreover, binding site analysis performed with S. nonagrioides larvae revealed that Cry1F and Cry1Ab proteins have different high-afÞnity binding sites (González-Cabrera et al 2006), making the development of cross-resistance unlikely.…”
Section: Discussionsupporting
confidence: 80%
“…Instead of incorporating the Bt-protein uniformly in the diet, it is added to the surface of the diet (e.g., Marçon et al, 1999;Siegfried et al, 2000Siegfried et al, , 2005Farinós et al, 2004Farinós et al, , 2011Farinós et al, , 2012Blanco et al, 2008;Gaspers et al, 2011). Important advantages of the surface treatment are the lower amount of Bt-protein required for each test and the reduction in costs associated with Btprotein preparation (Blanco et al, 2008).…”
Section: Resistance Evolution To the Cry34ab1/cry35ab1 Proteins In Comentioning
confidence: 99%
“…Baseline data should be established preferably before the first introductions of maize 59122, but at least during the initial years of its launch prior to high market penetration. Ideally, the same areas should be monitored over time to reduce the natural geographical variation in susceptibility (Farinós et al, 2004(Farinós et al, , 2011(Farinós et al, , 2012Saeglitz et al, 2006;Gaspers et al, 2011). Appropriately designed sampling strategies should account for the abundance, distribution and dispersal behaviour of WCR, and local variability in susceptibility levels.…”
Section: Resistance Evolution To the Cry34ab1/cry35ab1 Proteins In Comentioning
confidence: 99%
“…Annual assessments of ECB/MCB susceptibility to Cry1Ab in the USA and EU have not revealed any significant change in susceptibility or identified populations that survive on Cry1Ab-expressing Bt-maize plants (after more than ten years of exposure to the Cry1Ab protein in the USA) (Farinós et al, 2004(Farinós et al, , 2011Stodola et al, 2006;Andreadis et al, 2007;Siegfried et al, 2007;Crespo et al, 2009Crespo et al, , 2010EFSA Panel on Genetically Modified Organisms, 2011a, 2012a, 2013cSiegfried and Hellmich, 2012). Annual assessments of ECB/MCB susceptibility to Cry1Ab in the USA and EU have not revealed any significant change in susceptibility or identified populations that survive on Cry1Ab-expressing Bt-maize plants (after more than ten years of exposure to the Cry1Ab protein in the USA) (Farinós et al, 2004(Farinós et al, , 2011Stodola et al, 2006;Andreadis et al, 2007;Siegfried et al, 2007;Crespo et al, 2009Crespo et al, , 2010EFSA Panel on Genetically Modified Organisms, 2011a, 2012a, 2013cSiegfried and Hellmich, 2012).…”
Section: Cited Scientific Publicationsmentioning
confidence: 99%